IMPLEMENTASI KLAUSULA DIKUASAI OLEH NEGARA DALAM PASAL 33 UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 DALAM PRAKTEK KETATANEGARAAN INDONESIA - Muhammad Fazry (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This study aims to explore and discover how the implementation of the clause "controlled by the state" in article 33 of the 1945 Constitution of the Republic of Indonesia in the practice of Indonesian integrity. And what factors influence the implementation of the clause "controlled by the state" in article 33 of the 1945 Constitution of the Republic of Indonesia in Indonesian constitutional practice. This writing focuses on how the implementation of State control in article 33 of the 1945 Constitution. And find out what factors influence the implementation of state control in practice. This research is a normative study using a statute aproach approach, and a conceptual approach. By using a qualitative descriptive analysis model as an analysis knife. The research subject is Article 33 of the 1945 Constitution, especially in the "controlled by the State" clause.